Study on the time-varying fatigue reliability of the invert structure of subway tunnel under the action of train loads - Chen, Zhaofeng; Xu, Linrong; Huang, Changxi; Wu, Lei; Shang, Yonghui (Frontiers in Earth Science, 2023)
This paper presents an investigation of the fatigue reliability of the subway tunnel's invert structure under the influence of train loads. The analysis combines the use of higher-order moment theory, fatigue equation, and cumulative damage theory. The results show that reinforcing the invert structure is necessary under tension stress but not compression stress. The findings also reveal that the train's axle weight and speed have a significant impact on the fatigue reliability index, with speed having a slightly greater effect than axle weight. However, the thickness of the lining has a negligible effect on the reliability index. Over time, the fatigue reliability index continuously decreases, resulting in an increasing probability of failure. Therefore, it is crucial to inspect and maintain the tensile state of the invert structure, which is the area that requires the most attention.